(untitled) (Advancements in Homeopathic Research, 2022)
It is a chronic inflammatory disease of piloseabaceous gland which generally occurs in adolescence, consists of various skin disorders in the form of non inflammatory lesions (whiteheads, blackhead), superficial inflammatory lesions (papules, pustules superficial) and in inflammatory lesions (nodules), premises where predilection: face, neck, upper arms, chest and back.1Acne vulgaris is an inflammatory structural disorder of the sebaceous gland or follicles of the skin.2We have good scope in homoeopathy for both acne recurrence and psychosocial life.